An Iterative Quality Improvement Process Improves Pediatric Ward Discharge Efficiency - Hamline, Michelle Y. (Hosp Pediatr, 2020)
OBJECTIVES: Discharge of hospitalized pediatric patients may be delayed for various “nonmedical” reasons. Such delays impact hospital flow and contribute to hospital crowding. We aimed to improve discharge efficiency for our hospitalized pediatric patients by using an iterative quality improvement (QI) process. METHODS: Opportunities for improved efficiency were identified using value stream mapping, root cause, and benefit-effort analyses. QI interventions were focused on altered physician workflow, standardized discharge checklists, and physician workshops by using multiple plan-do-study-act cycles. The primary outcome of percentage of discharges before noon, process measure of percentage of discharges with orders before 10 am, and balancing measures of readmission rate, emergency department revisit rate, and parent experience survey scores were analyzed by using statistical process control. The secondary outcome of mean length of stay was analyzed using t tests and linear regression. RESULTS: Implementation of our interventions was associated with special cause variation, with an upward shift in mean percentage of discharges before noon from 13.2% to 18.5%. Mean percentage of patients with discharge orders before 10 am also increased from 13.6% to 23.6% and met rules for special cause. No change was detected in a control group. Adjusted mean length of stay index, 30-day readmissions, and parent experience survey scores remained unchanged. Special cause variation indicated a decreased 48-hour emergency department revisit rate associated with our interventions. CONCLUSIONS: An iterative QI process improved discharge efficiency without negatively affecting subsequent hospital use or parent experience. With this study, we support investment of resources into improving pediatric discharge efficiency through value stream mapping and rapid cycle QI.